Respiratory gated diffusion-weighted imaging of the liver: value of apparent diffusion coefficient measurements in the differentiation between most commonly encountered benign and malignant focal liver lesions. - Gourtsoyianni S; Papanikolaou N; Yarmenitis S; Maris T; Karantanas A; Gourtsoyiannis N; Gourtsoyianni, Sofia; Papanikolaou, Nickolas; Yarmenitis, Spyros; Maris, Thomas; Karantanas, Apostolos; Gourtsoyiannis, Nicholas (European Radiology, 2008)
The purpose of this study was to measure apparent diffusion coefficient values of normal liver parenchyma and focal liver lesions utilizing a respiratory gated diffusion sequence with multiple b-values and to investigate whether apparent diffusion coefficient (ADC) measurements may be utilized to characterize and differentiate between malignant and benign focal hepatic lesions. Thirty-eight consecutive patients underwent MRI of the liver including diffusion-weighted imaging (DWI). A single-shot echo planar imaging sequence was applied in coronal orientation with multiple b-values (0, 50, 500, 1,000 s/mm2) and respiratory gating. ADC values were recorded on corresponding maps utilizing region of interest measurements in patients with benign (group A), malignant (group B) focal lesions and liver parenchyma (group C). Statistical analysis was applied to check whether differences in mean ADC values were significant (p<0.05). No focal lesions were detected in 11 patients, with a mean ADC value (CI 95%) of liver parenchyma 1.25x10(-3) mm2/s (1.21x10(-3) mm2/s-1.29x10(-3) mm2/s). Differences in mean ADC of liver parenchyma between group A and B were not significant (p=0.054, 1.30x10(-3) mm2/s and 1.31x10(-3) mm2/s, respectively). Mean ADC value (95% CI) of 22 benign lesions found in 18 patients was 2.55x10(-3) mm2/s (2.35x10(-3) mm2/s-2.74x10(-3) mm2/s), while the mean ADC value (95% CI) of 16 malignant lesions recorded in 9 patients was 1.04x10(-3) mm2/s (0.9x10(-3) mm2/s-1.17x10(-3) mm2/s). The difference between mean ADC values of benign and malignant focal lesions was statistically significant (p<0.0001). Respiratory gated diffusion-weighted imaging in the liver is technically feasible. Apparent diffusion coefficient measurements can be useful in differentiating malignant from benign focal liver lesions.